Revitalizing established teaching and assessment methods in oncological rehabilitation comprehensive laboratory course - Li, Yang; Li, Xiao-meng; Liang, Hong; Wei, Qian (Frontiers in Education, 2024)
In the reform of medical laboratory courses, innovative teaching methods and the development of a teaching assessment system are crucial. However, in past practices, assessments have encountered some issues: a greater emphasis on recording outcomes, neglecting supervision of the process; a focus on summarizing writing, overlooking the importance of analysis and improvement. In the teaching process of Jilin University's Oncological Rehabilitation Experimental Teaching Demonstration Center, the Peer-Assisted Learning (PAL) model is employed to enhance students' learning approaches. The innovative incorporation of Direct Observation of Procedural Skills (DOPS) and Mini-Clinical Evaluation Exercise (Mini-CEX) facilitates effective assessment and feedback. The combination of these reform measures not only addresses issues in experimental teaching but also enhances the internalization of students' knowledge and skills. In this study, we applied the evaluation systems of Direct Observation of Procedural Skills and Mini-Clinical Evaluation Exercise (Mini-CEX) to the comprehensive laboratory course in oncological rehabilitation. We utilized questionnaires to assess the impact of these reforms on students, aiming to evaluate the effectiveness of the course modifications.Statistical analysis of the data revealed a high level of student approval and a strong willingness to learn under the new evaluation system. Compared to traditional teaching methods, the introduction of DOPS and Mini-CEX significantly enhanced students' overall competencies and improved the quality of the oncological rehabilitation course. Our approach represents an innovative reform, suggesting that incorporating DOPS and Mini-CEX into teaching could provide a widely applicable and promising new educational method. This paper explores and systematically elaborates on the reform and practice of the teaching model and formative assessment in the comprehensive laboratory course of oncological rehabilitation.